Maqasid al-Syar’iah - Sari, Dian Amelia; Rahman, Ahmad Fadly; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The discussion of Maqashid Al-Syari'ah, or the purpose of Islamic law, is an important discussion that has received great attention from Islamic scholars and legal experts. Some scholars include this topic in the study of ushul fiqh, while others discuss it as a separate material and expand it in the context of Islamic legal philosophy. If examined, all of Allah's commands and prohibitions in the Qur'an, as well as the teachings and prohibitions of the Prophet Muhammad SAW in the sunnah which are arranged in fiqh, clearly have a specific purpose and none of them are in vain. All these rules have deep wisdom, namely as a form of mercy for humanity, as confirmed in several verses of the Koran, including Surah Al-Anbiya' verse 107 which explains the purpose of the sending of the Prophet Muhammad. In this verse, mercy for all nature is defined as the benefit of the people. In simple terms, benefit can be interpreted as something that is good and accepted by common sense. The meaning of